2012
DOI: 10.1242/dmm.010512
|View full text |Cite
|
Sign up to set email alerts
|

Functional and histopathological identification of the respiratory failure in a DMSXL transgenic mouse model of Myotonic Dystrophy

Abstract: SUMMARYAcute and chronic respiratory failure is one of the major and potentially life-threatening features in individuals with myotonic dystrophy type 1 (DM1). Despite several clinical demonstrations showing respiratory problems in DM1 patients, the mechanisms are still not completely understood. This study was designed to investigate whether the DMSXL transgenic mouse model for DM1 exhibits respiratory disorders and, if so, to identify the pathological changes underlying these respiratory problems. Using pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 63 publications
(87 reference statements)
2
24
0
Order By: Relevance
“…Thus, this is a precious model to study the time course of the disease with aging. It has been previously shown that DMSXL mice have reduced muscle strength, lower motor performances, peripheral neuropathy and respiratory impairments [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this is a precious model to study the time course of the disease with aging. It has been previously shown that DMSXL mice have reduced muscle strength, lower motor performances, peripheral neuropathy and respiratory impairments [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The originality of this model lies in the pattern of expression of the DMPK gene in DMSXL which is similar to DM1 patients including a high level of expression in the heart [13]. This model reproduces the main clinical characteristics observed in the human disease including reduced muscle strength, lower motor performances, peripheral neuropathy and respiratory impairments [13][14][15]. However, nothing is known about the cardiac phenotype of the DMSXL mouse.…”
Section: Introductionmentioning
confidence: 99%
“…Lung function parameters (respiration rate, tidal volume, and airflow rate) were measured using Respiromax, Columbus Instruments . Rats were acclimatized for 15 days before the measurement of lung function parameters.…”
Section: Methodsmentioning
confidence: 99%
“…54 They also suggest that the postnatal respiratory insufficiency in CDM patients may be due to the defects of diaphragm muscle. 55 We next characterized the growth profiles of DSMD-QKO SC mice. Interestingly, DSMD-QKO SC pups exhibited growthretarded phenotype (Supplementary information, Fig.…”
Section: Mice Carrying Quadruple Mutations Show Typical Symptoms In Cmentioning
confidence: 99%